THE COMPARISON OF OPEN AND LAPAROSCOPIC VENTRAL HERNIA REPAIRS - Khan, Jehangir Sarwar; Qureshi, Usman; Farooq, Umar; Hassan, Zahra Fatima; Hassan, Hamid (Journal of Postgraduate Medical Institute, 2012)
Objective: To compare the outcome of open versus laparoscopic ventral hernia repair in terms of duration of surgery, post operative pain and length of hospital stay. Methodology: A comparative study was carried out at in-patients presenting at Surgical Departments of Benazir Bhutto Hospital, Holy Family Hospital and author's clinics . A total of 100 patients were included in the study and the patients were divided randomly in Group A and Group B, having 50 patients in each group, Group A representing open mesh repair group and Group B laparoscopic repair group. Patients of both groups were observed per-operatively for duration of surgery, postoperatively for length of hospital stay and intensity of postoperative pain. Results: There was no statistically significant difference between two groups for duration of surgery (P>0.96). Pain was calculated at 2 and 24 hour, using visual analogue scale. Less pain was noted in Group B. Difference of pain score was statistically significant at 2h and 24h (P0< .05). Average duration of postoperative stay in hours was more in Group A (39.6 hrs) as compared to Group B (31.4 hrs) (P <0.05). Conclusion: Laparoscopic ventral hernia repair is beneficial due to less post operative pain and short duration of post operative hospital stay but duration of surgery remained same in both the settings.